Mixed marriages between European free movers - Gaspar, Sofia (2009)
In this paper I analyze some of the issues that enable the understanding of European intra-marriage as a social phenomenon, by presenting some preliminary empirical findings resulting from on-going qualitative research being carried out in Lisbon. This paper presents a very clear structure, as follows: firstly, I will explain how free movers may be seen as an emerging social group within the European matrimonial market. Afterwards, I will clarify how the term European intra-marriage better categorizes this new type of mixed unions. Thirdly, I will clarify what methodological procedures have been used so far. And finally, I will describe certain results that can shed light on some of the dimensions under evaluation with regard to European mixed unions. In the final section, I will provide some lines of research that need to be taken into consideration when investigating this subject further.